Economically and thermodynamically efficient pressure-swing distillation with heat integration and heat pump techniques. (5th January 2023) - Zhai, Jian; Chen, Xin; Sun, Xiaoqing; Xie, Hongfei
Highlights: Pressure-swing distillation is intensified with heat integration and heat pump. Designs are evaluated from economic, thermodynamic, and environmental perspectives. Heat pump-assisted pressure-swing distillation gives the best performance. Reliability of compression process in heat pump working process is analysed. Abstract: The recovery of isopropanol from wastewater is of significance in the industry in light of sustainable development and public health. In this study, the separation has been investigated in the pressure-swing distillation process to avoid contamination by the additional solvent. To address the problem of tremendous energy consumption in conventional pressure-swing distillation, three energy-efficient pressure-swing distillation processes were proposed based on heat integration and heat pump techniques. For each scheme, the sequential iterative optimisation was performed targeting the minimum total annual cost. The temperature-enthalpy diagrams were employed to analyse the energy consumption of the proposed configurations. The reliability of the compression process in the compressor was ensured by means of the temperature-entropy diagrams. All pressure-swing distillation designs were compared from the economic, thermodynamic, and environmental perspectives. In comparison with the proposed conventional pressure-swing distillation, the heat integration and heat pump can save 31.44% and 51.30% total annual cost with a capital payback period of 3 years, respectively. Special attention was paid to evaluating a combined utilization of heat integration and heat pump techniques which can reduce 38.30% of the total annual cost. The savings in the total annual cost of all intensified designs were expected enhanced for a longer payback period. Besides, all alternative designs were found with good performance in decreasing CO2 emissions and enhancing thermodynamic efficiency. The present study can serve as a reference for designing other azeotrope separations to achieve sustainable development.